Quota Formula-Data Update and Further Considerations. (Policy Papers; Policy Paper ;, 2014)
The IMF staff has updated individual member country data for the variables used in the quota formula for the period 2000-12. The updated database also incorporates the recently released 2011 International Comparison Program (ICP) global estimates for purchasing power parity rates (PPP) rates. The staff paper also presents updated calculated quota shares based on the current quota formula. The current quota formula includes a GDP variable, which is a blend of GDP at market rates and GDP at purchasing power parity (PPP), openness, variability, and international reserves. The International Monetary and Financial Committee has called for agreement on a new quota formula as part of the 15th General Review of Quotas. The paper presents a limited set of illustrative simulations of possible reforms of the quota formula using the updated quota data. These simulations are purely illustrative and do not represent proposals. The new data tables that can be downloaded via the below link include also the comparable value of each variable for the previous quota dataset, which was based on data covering the period 1999-2011. The information is presented in millions of SDRs (Table A1) and in percent of their respective global totals (Tables A2 and A3). A table showing calculated quota shares based on the current quota formula is also included (Table A4). Data sources and a description of the quota variables are discussed in Quota Formula - Data Update and Further Considerations - Statistical Appendix; IMF Policy Paper; July 2014. Download Quota Data: Updated IMF Quota Formula Variables - July 2014.